Synthesis of novel 6,7-dimethoxy-4-anilinoquinolines as potent c-Met inhibitors - Qing-Wen Zhang; Zi-Dan Ye; Chang Shen; Hong-Xia Tie; Lei Wang; Lei Shi (Taylor & Francis Group, 2019)
HGF/c-Met signalling pathway plays an important role in the development of cancers. A series of 6,7-dimethoxy-4-anilinoquinolines possessing benzimidazole moiety were synthesised and identified as potent inhibitors of the tyrosine kinase c-Met. Their in vitro biological activities against three cancer cell lines (A549, MCF-7, and MKN-45) were also evaluated. Most of these compounds exhibited moderate to remarkable potency. Among them, compound 12n showed the most potent inhibitory activity against c-Met with IC50 value of 0.030 ± 0.008 µM and it also showed excellent anticancer activity against the tested cancer cell lines at low micromolar concentration. Molecular docking verified the results and revealed the possible binding mode of the most promising compound 12n into the ATP-binding site of c-Met kinase.